Joint optimization of power and channel access in cognitive radio network - Jiang ZHU; Qingmin DU; Shaowei BA (Dianxin kexue)
In cognitive radio networks,according to the problem of all users can access the same channel to communicate,two joint optimization schemes for different scenarios were proposed.When the system is infeasible,a scheme of joint optimal power and admission control was proposed.As admission control is the NP problem,the LP-SO was used to achieve optimize control.At the same time,the convergence of the proposed algorithm was analyzed and proved.When the system is feasible,a scheme of joint optimal power and transmission rate allocation was proposed,using the improved Lagrange duality algorithm to achieve optimize control.The numerical results show that compared with other admission control algorithms,the time complexity of proposed algorithm is increased,but it can converge quickly,effectively improves the number of admitted uses while reducing power consumption.In addition,the proposed algorithm can allocate transmission rate more fairly.